2014
DOI: 10.1016/j.biomaterials.2013.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Dextran derivative-based pH-sensitive liposomes for cancer immunotherapy

Abstract: pH-Sensitive dextran derivatives having 3-methylglutarylated residues (MGlu-Dex) were prepared by reacting dextran with 3-methyl-glutaric anhydride. MGlu-Dex changed the protonation state and their characteristics from hydrophilic to hydrophobic in neutral and acidic pH regions. Surface modification of egg yolk phosphatidylcholine liposomes with MGlu-Dex produced highly pH-sensitive liposomes that were stable at neutral pH but which were destabilized strongly in the weakly acidic pH region. MGlu-Dex-modified l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
111
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(115 citation statements)
references
References 31 publications
3
111
1
Order By: Relevance
“…Many methods have been developed to synthesize pH-responsive MSNs systems and pH-sensitive lipid membrane as drug carriers to deliver drugs and trigger the release of encapsulated drugs in tumor cells, an important role in all drug delivery systems. [14][15][16][17] The pH-sensitive lipid membrane that target tumors are stable at physiological pH values, but are designed to become unstable under acidic conditions, resulting in the release of their drug cargo. 18 Some studies have shown that coated nanoparticles of pH-sensitive lipid membrane can protect the drug and increase the drug concentration, which is favored to decrease systemic toxicity and enhance antitumor activity.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods have been developed to synthesize pH-responsive MSNs systems and pH-sensitive lipid membrane as drug carriers to deliver drugs and trigger the release of encapsulated drugs in tumor cells, an important role in all drug delivery systems. [14][15][16][17] The pH-sensitive lipid membrane that target tumors are stable at physiological pH values, but are designed to become unstable under acidic conditions, resulting in the release of their drug cargo. 18 Some studies have shown that coated nanoparticles of pH-sensitive lipid membrane can protect the drug and increase the drug concentration, which is favored to decrease systemic toxicity and enhance antitumor activity.…”
Section: Introductionmentioning
confidence: 99%
“…11 In fact, the ability to control and produce a burst release of the encapsulated drug from liposomes would be extremely advantageous and may prove to be an essential step in providing effective levels of drug in the tumor. 12 Several approaches for triggered drug release from liposomes have been investigated, such as enzyme-activated, 13,14 pH-sensitive, 15,16 lightsensitive, 17,18 ultrasound-triggered, [19][20][21] and thermosensitive liposomes. [22][23][24][25][26][27][28][29][30] Thermosensitive liposomes can be prepared from phospholipids that exhibit a sharp gel-to-liquid crystalline transition.…”
Section: Introductionmentioning
confidence: 99%
“…Surface modification of phosphatidylcholine liposomes with MGlu-Dex enabled obtaining highly pH-sensitive liposomes that were stable at neutral pH but were strongly destabilized in the weakly acidic pH region (pH ~5.5). In vivo data suggested that compared to unmodified liposomes, MGlu-Dex-ovalbumin liposomes efficiently increased the uptake of ovalbumin by dendritic cells and significantly suppressed tumor growth [58].…”
Section: Internal Stimulimentioning
confidence: 99%